2015
DOI: 10.4085/1052-6050-50.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Days to Return to Participation After a Hamstrings Strain Among American Collegiate Soccer Players

Abstract: Context: Among US collegiate soccer players, the incidence rate and the event characteristics of hamstrings strains differ between sexes, but comparisons in the return-to-participation (RTP) time have not been reported.Objective: To compare the RTP time between male and female collegiate soccer players and analyze the influence of event characteristics on the RTP time for each sex.Design: Descriptive epidemiology study. Setting: Data were collected from collegiate teams that voluntarily participated in the Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Recovery time was similar between sexes for adductor strains and ankle lateral sprains. Previous studies in football players have not found sex differences in return to play time from ACL injury or hamstring strain, even though there is evidence suggesting that women recover slower from concussions . However, this question remains to be answered under more strict experimental conditions, controlling for initial injury severity and standardizing return to play protocols.…”
Section: Discussionmentioning
confidence: 95%
“…Recovery time was similar between sexes for adductor strains and ankle lateral sprains. Previous studies in football players have not found sex differences in return to play time from ACL injury or hamstring strain, even though there is evidence suggesting that women recover slower from concussions . However, this question remains to be answered under more strict experimental conditions, controlling for initial injury severity and standardizing return to play protocols.…”
Section: Discussionmentioning
confidence: 95%
“…Along those lines, strength training is also crucial for improving muscular strength and power, which aids in the reduction of exposure to sustaining hamstring injuries [28]. A study by Askling et al [29] investigated the effects of short-term strength training on hamstring injuries and recovery. Concurrently, a study by Ertelt et al [28] examined the impact of a 4-week strength training program on hamstring injuries in female soccer players.…”
Section: Impact Of Resistance Training On Hamstring Injuriesmentioning
confidence: 99%
“…Descriptive epidemiologic investigations of men's and women's soccer injuries using NCAA ISS data were published in 2007. 18,19 National Collegiate Athletic Association ISS data from 2004 through 2009 were also used in 2 investigations 20,21 of hamstrings injuries in soccer players. Additionally, these data have been cited in at least 35 publications that addressed a range of collegiate athletes' injuries.…”
Section: Surveillance Of Overuse Injuriesmentioning
confidence: 99%
“…As a result, almost all injuries were to the lower extremity (which accounted for 80% of the total overuse mechanisms of injury in soccer players). 21 The restriction to time-loss medical-attention injuries was necessary considering that the data originated from the NCAA ISS, which used this injury definition until 2009.…”
Section: Recommendations For Surveillance Of Overuse Injuriesmentioning
confidence: 99%